EXAMINATION OF THE IMPORTANCE OF BRANDS FOR CONSUMER PERCEPTIONS OF SELF-EMERGING MARKETS - Gandhi, Rishabh (2010)
This research aims to find the consumer perceptions of a brand in an self-emerging market. The study will be focusing on India which is a self-emerging market and the Indian consumers perceptions of local and foreign brands. This research also covers a lot of different areas relating to brands, country of origin of the brand and globalisation. The emerging markets and the Indian markets have been studied in depth the strategies brands use to succeed in these markets. Interviews of Indian consumers from different parts of India have been taken to find out their perceptions of the brands in India